Genome-wide characterization of ascorbate peroxidase gene family in pepper (Capsicum annuum L.) in response to multiple abiotic stresses - Pang, Xin; Chen, Jun; Xu, Yang; Liu, Jia; Zhong, Yangmin; Wang, Linlin; Zheng, Jiaqiu; Wan, Hongjian (Frontiers in Plant Science, 2023)
Pepper is widely grown all over the world, so it faces many abiotic stresses, such as drought, high temperature, low temperature, salt damage and so on. Plant stresses causing accumulation of reactive oxidative species (ROS) are removing by antioxidant defense systems, and ascorbate peroxidase (APX) is an important antioxidant enzyme. Therefore, the present study performed genome-wide identification of APX gene family in pepper. We identified 9 members of the APX gene family in the pepper genome according the APX proteins conserved domain of Arabidopsis thaliana. The physicochemical property analysis showed that CaAPX3 had the longest protein sequence and the largest molecular weight in all genes, while CaAPX9 had the shortest protein sequence and the smallest MW. The gene structure analysis showed that CaAPXs were composed of 7-10 introns. CaAPX genes were divided into four groups. The APX genes of Group I and group IV were localized in the peroxisomes and chloroplasts, respectively, the group II genes were localized in the chloroplasts and mitochondria, and the group III was located in the cytoplasm and extracell. The conservative motif analysis showed that all APX genes in the pepper had motif 2, motif 3 and motif 5. The APX gene family members were distributed on five chromosomes (Chr. 2, 4, 6, 8, 9). The cis-acting element analysis showed that most CaAPX genes contain a variety of cis-elements related to plant hormones and abiotic stress. RNA-seq expression analysis showed that the expression patterns of nine APXs were different in vegetative and reproductive organs at different growth and development stages. In addition, the qRT-PCR analysis of the CaAPX genes revealed significant differential expression in response to high temperature, low temperature, and salinity stresses in leave tissue. In conclusion, our study identified the APX gene family members in the pepper and predicted the functions of this gene family, which would provide resources for further functional characterization of CaAPX genes.